PENGARUH KOMBINASI PIJAT ENDORPHIN DAN AROMATHERAPI LAVENDER TERHADAP NYERI LUKA POST SECTIO CAESARIA PADA IBU PRIMIPARA DI RSUD PANDAN ARANG BOYOLALI - Puput Kurnia Sari; Arisda Candra Satriwati; Aulia , Aulia; Niken Wahyu Hidayati; Sitti Sarti (Journal of Innovation Research and Knowledge, 2024)
Background: Sectio Caesaria causes several complaints that may arise, one of which is surgical wound pain. Non-pharmacological methods that are expected to overcome are endorphin massage and lavender aromatherapy. Objective: to find out the effect of the combination of endorphin massage and lavender aromatherapy on post section cesarean wound pain in primiparous mothers at Pandan Arang Boyolali Hospital. Method: Quasy Experimental research design, one group pre post test design. The population of this research is all mothers who gave birth with SC primipara at RS Pndan Arang Boyolali in January 2023 to February 2023, a total of 24 respondents. The sample uses the Federer formula with a total of 18 respondents. Purposive sampling technique. Bivariate analysis using Wilcoxon. Results: Post cesarean section wound pain before the combination of endorphin massage and lavender aromatherapy had a median of 5. caesarean section in mothers at RS JIH Solo (0.000<0.05). Conclusion: the effect of a combination of endorphin massage and lavender aromatherapy on the reduction of post section cesarean wound pain in mothers at RS Pandan Arang Boyolali. It is expected that postpartum mothers can use the combination of endorphin massage and camomile aromatherapy to empower the family in reducing anxiety in postpartum mothers by asking for help from their husbands, mothers or close people